Evaluating Teaching Quality in Colleges and Universities of Public Art Education Using the AHP Fuzzy Comprehensive Method - Yu, Yan (Scientific programming, 2022)
The effectiveness of classroom teaching has emerged as the determining factor in whether a school will endure as higher education in China develops. Currently, all schools and institutions have established public art education classes that offer art education to students who do not study art. With the establishment of public art education, students of other subjects can learn art, film and television, music, calligraphy, dance, and drama and master basic practical skills that fundamentally improve their aesthetic capacity and qualities that promote the emergence of morality, intelligence, physique, and glamour among college students. However, colleges and universities should assess the teaching abilities of teachers after establishing public art education programs and then improve their own teaching abilities by fully altering the public art education model in accordance with the results of the teaching evaluation quality score. This study establishes a method for evaluating the effectiveness of teaching in public art education courses at colleges and institutions. The fuzzy comprehensive is based on the analytic hierarchy process (AHP). The system for evaluating the quality of teaching is established, which builds the teacher’s teaching evaluation factor set, decides how much weight each teacher’s teaching quality evaluation factor should have, establishes the teaching quality evaluation grade, and decides the comprehensive teaching quality evaluation method. The teaching quality evaluation is finally computed using the fuzzy comprehensive evaluation formula and the AHP approach in accordance with the evaluation results provided by five different types of experts. The results indicate that department leaders awarded teachers a 94.11 rating for their ability to teach.